Diagnostic value of immunohistochemistry for the detection of the BRAFV600E mutation in papillary thyroid carcinoma: comparative analysis with three DNA-based assays - Ilie, Marius I.; Lassalle, Sandra; Long-Mira, Elodie; Bonnetaud, Christelle; Bordone, Olivier; Lespinet, Virginie; Lamy, Aude; Sabourin, Jean-Christophe; Haudebourg, Juliette; Butori, Catherine; Guevara, Nicolas; Peyrottes, Isabelle; et al. (Thyroid, 2014)
Background: The aim of this study was to compare the detection of BRAFV600E by immunohistochemistry (IHC) using a mutation-specific antibody with molecular biology methods for evaluation of papillary thyroid carcinoma (PTC) patients.Patients and methods: This study concerned 198 consecutive conventional PTC patients, of which the majority were women (133/198; 67%), with a mean age of 56 years (range 19-79 years). BRAF mutation analysis was performed using DNA-based (direct sequencing, pyrosequencing, and SNaPshot) and IHC (VE1 antibody) methods. The sensitivity and specificity of IHC for BRAFV600E was compared with the molecular biology data.Results: A BRAF mutational result was obtained in 194 cases. A BRAFV600E mutation was detected in 153/194 (79%) cases of PTC when using at least one molecular method, and in 151/194 (78%) cases with IHC. No false positive results were noted using IHC to detect the BRAFV600E mutation. Besides this mutation, other rare BRAF mutations (BRAFV600K and BRAFK601E), used as negative controls, were consistently negative with IHC. The sensitivity and specificity of IHC for the detection of this mutation were 98.7% and 100% respectively. The IHC test demonstrated excellent performance at a level equivalent to two DNA-based counterparts (pyrosequencing and SNaPshot). Failure to achieve a result was more frequent with the direct sequencing method than with the three other methods.Conclusion: IHC using the VE1 antibody is a specific and sensitive method for the detection of the BRAFV600E mutation in PTC. IHC may be an alternative to molecular biology approaches for the routine detection of this mutation in PTC patients.
Im Titel ist "V600E" nach BRAF hochgestellt
Gesehen am 12.10.2020